2013
DOI: 10.1177/0269216313488989
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for treatment, care and information if faced with serious illness: A comparative population-based survey in seven European countries

Abstract: Across all countries, extending life was prioritised by a minority, regardless of health status. Treatment and care needs to be reoriented with patient education and palliative care becoming mainstream for serious conditions such as cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 40 publications
(71 reference statements)
3
89
0
10
Order By: Relevance
“…However, recent evidence suggests that control of pain and not being a burden are the important priorities for patients and the public. 33,79,83 Moreover, pain is reported to be best controlled in hospice, then hospital, and least well at home. 61 As people get older, they report an increased preference to die in hospice.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
“…However, recent evidence suggests that control of pain and not being a burden are the important priorities for patients and the public. 33,79,83 Moreover, pain is reported to be best controlled in hospice, then hospital, and least well at home. 61 As people get older, they report an increased preference to die in hospice.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
“…This is particularly the case for patients with non-cancer conditions, which are often characterised by relapses and remissions and have a less predictable dying phase. However, most people, if faced with a serious illness and little time to live, would choose to prioritise quality of life over extending the amount of time left, 4 and an inability to accurately predict prognosis should not therefore preclude initiating an honest discussion of the likely outcomes, while acknowledging the uncertainty. Delaying such discussions until the patient is imminently dying makes it much less likely that the patient's preferences for end-of-life care will be met: patients who have late discussions concerning end-of-life care with their physicians are more likely to receive aggressive care close to death.…”
Section: Barriers To End-of-life Communicationmentioning
confidence: 99%
“…A Europe‐wide survey of more than 9000 people showed that QoL was found more important than quantity of life (71% vs 4%). The remaining 25% found that QoL and quantity of life were equally important . A similar American study “Living well at the end of life” revealed that 71% of the surveyed people preferred to enhance QoL, even if that would mean living a shorter life.…”
Section: Resultsmentioning
confidence: 98%